Impact of drinking water treatment and distribution on the microbiome continuum : an ecological disturbance's perspective - Zhang, Ya (2019)
While microbes are known to be present at different stages of a drinking water system, their potential functions and ability to grow in such systems are poorly understood. In this study, we demonstrated that treatment and distribution processes could be viewed as ecological disturbances exhibited over space on the microbiome continuum in a groundwater‐derived system. Results from 16S rRNA gene amplicon analysis and metagenomics suggested that disturbances in the system were intense as the community diversity was substantially reduced during the treatment steps. Specifically, syntrophs and methanogens dominant in raw water (RW) disappeared after water abstraction, accompanied by a substantial decrease in both the abundance and number of functional genes related to methanogenesis. The softening effluent was dominated by an Exiguobacterium‐related population, likely due to its ability to use the phosphotransferase system (PTS) as regulatory machinery to control the energy conditions of the cell. After disinfection and entering the distribution system, community‐level functionality remained relatively stable, whereas the community structure differed from those taken in the treatment steps. The diversity and high abundance of some eukaryotic groups in the system suggested that predation could be a disturbance to the bacterial microbiome, which could further drive the diversification of the bacterial community.